The location, expression and regulation of three antibiotic resistance genes in acinetobacter - Elisha, Brenda Gay (Division of Medical Microbiology, 2023)
Clinical isolates of Acinetobacter often exhibit resistance to many antibiotics, including the aminoglycosides and chloramphenicol. Yet very little is known about this resistance at the molecular level. A strain of Acinetobacter baumannii (strain SAK) was isolated from a tracheal aspirate; it is resistant to gentamicin, tobramycin, netilmicin, streptomycin, chloramphenicol and suphamethoxazole. This study examines the nature of the resistance to gentamicin, tobramycin and chloramphenicol at three levels: the biochemical mechanism of resistance, the location of the resistance genes, and the expression and regulation of these genes. Two aminoglycoside resistance genes, and a chloramphenicol resistance gene have been identified in strain SAK. The aminoglycoside resistance genes, aadB and aacC, encode AAD (2") and AAC(3), respectively. Both of the enzymes have activity against gentamicin and tobramycin. DNA: DNA hybridization with specific DNA probes indicates that the aadB gene is in the chromosome, whereas the aacC and cat genes have a plasmid and a chromosomal locus. Each of these genes was cloned and expressed in E. coli. Interestingly, although the aadB gene is functional ·in E.coli, RNA studies indicate that it is not expressed in strain SAK. Only aacC gene transcripts were detected in this strain. Thus, strain SAK contains a seemingly redundant aadB gene. DNA sequencing data show that the aadB gene is part of a Tn2J-like transposon; similarly, the cat gene is also part of a transposon which may be identical to Tn2670. In a limited study, it was not possible to activate the aadB gene in strain SAK. There is DNA sequencing evidence to suggest that the aacC gene may be linked to an IS, and that it may have a catabolite sensitive promoter. Papers based on the work described in this dissertation have been accepted for publication. in: Plasmid (Elisha,B.G. & Steyn,L.M., 1991); Current Microbiology (Elisha,B.G. & Steyn,L.M., 1991); FEMS Symposium Series: The Biology of Acinetobacter. K.J.Towner & C.A.Fewson (eds.). Plenum Press. New York. (Elisha,B.G. & Steyn,L.M., 1991).